ESPECIALLY THE CHOICE OF TOOTHPASTE TEENS - Lepsky, V.V. (World of Medicine and Biology, 2015)
Introduction. Today, toothpaste is a common means oral care. Toothpaste - a multi-component system, in which take part the formation of abrasive, wetting, foaming, surface active ingredients, preservatives, fillers, flavoring, water treatments and preventive elements. The ratio of these components determines the properties, function, and mechanism of action efficacy paste. Toothpaste is a complex substance that performs the basic functions: - Aesthetic - cleaning and polishing of the tooth surface; - Medical - removal of plaque; - Drugs - administration of a pharmacological substances. The immediate purpose of the toothpaste - cleansing surfaces of the teeth, gums, between the teeth, tongue of food debris, plaque, mucus removal of plaque and obstruction of microbial contamination by chemical and mechanical exposure. Depending on the structure and mechanism of action of toothpastes are divided into hygienic and prophylactic. On the recommendation of the World Health Organization (WHO), the optimal concentration of fluoride in the toothpaste is 0.1%. Toothpastes for adults contain from 0.11 to 0.76% Na and 0.38 to 1,14% Na monofluorophosphate. Baby tooth - paste up 0,023% F. The appearance on the Ukrainian market, a large number of toothpastes both domestic and foreign production became the basis for the study of 6-7 students and 10 classes of the school №11, the city of Cherkasy selection of certain toothpastes and the appropriateness of their use. The aim of our research - to analyze the modern approach of adolescents of all ages to the choice of toothpaste for brushing. Materials and methods. Developed an anonymous questionnaire for pupils of 6-7 and 10 classes, the analysis of which allows you to determine the frequency and type of use of toothpaste, and the reasons, according to which the preference of a particular pasta, how to identify the properties of pasta prefer the students that they like what taste, efficiency, consistency and other properties. What are the properties of the students would like to have the pasta: taste and more effective to clean the surface of the teeth. Who becomes a paste for cleaning teeth: the parents or student buys himself or the doctor recommends, advertising. The survey of students conducted in 6, 7, 10 and 11 classes of secondary school, only 75 students surveyed between the ages of 12-13 to 15 years. Results of the study. However, on the basis of the literature it is known that all the paste and affect a variety of different ways, some over the gum, some of the teeth. When the disease to be applied gums toothpastes containing grass. On the enamel pastes are not the same depending on the content of a paste: paste "Lacalut", "Sensodyne" eliminate tooth sensitivity, "LacalutWhite", "Sensodyne" and others - have whitening properties. Paste "New pearls", "Oral-BSensitiv", "Parodontol" contain mineralized additives. Most of these toothpastes contain fluoride or monofluorophosphate. The results of the survey of students grades 6-7 and 10 showed a preference for most pasta "Lacalut" and "Blend-a-med" (42,6%) due to the fact that they meet all necessary requirements.